A comparison of the Allen Cognitive Level Test and the Wisconsin Card Sorting Test in adults with schizophrenia. - Secrest, Lori; Wood AE; Tapp A (American Journal of Occupational Therapy)
Objective. This study examines the relationship among executive function, visuospatial problem solving, and measures of occupational functioning in 33 adult men with schizophrenia or schizoaffective disorder. Method. Three measures were administered in a onetime assessment session. The Wisconsin Card Sorting Test (WCST) was used to measure executive functioning, abstract reasoning, and problem-solving abilities. The Allen Cognitive Level (ACL) Test was used to measure learning, problem solving, and visuospatial abilities. The Routine Task Inventory (RTI) measured the level ofperformance in activities of daily living. Results. Using multiple regression controlling for age, the WCST significantly predicted performance on the ACL the RTI. Perseverative errors on the WCST were negatively correlated with the ACL (r = -.47) and RTI scores (r = -.59). The ACL and RTI were also significantly correlated (r = . 67). Conclusion. Both the WCST and the ACL are sensitive to similar domains of functioning and are predictive of task performance. The results support the use of the ACL as a quick measure of a person's cognitive and functional abilities.